2021
DOI: 10.1002/gea.21868
|View full text |Cite
|
Sign up to set email alerts
|

Mercury enrichment in anthrosols and adjacent coastal sediments at a Classic Maya site, Marco Gonzalez, Belize

Abstract: Elevated concentrations of total mercury (THg) are found in the surface soils and flanking wetland sediments at the Classic Maya coastal site of Marco Gonzalez, Belize. Significant concentrations (up to 1.3 µg·g−1 dry mass) of THg occur in leaf litter‐rich soils, as well as in the artefact‐rich anthrosol spread over the vegetated mound site of structures and occupation debris. The abundance and spatial pattern of major and trace elements measured in the surface soils indicate both site‐scale controlling factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 90 publications
0
7
0
Order By: Relevance
“…Instead, the changes in fertility and the accumulation of deposits seem to reflect unintentional behaviour -the detritus of living, working and dying. Work carried out between 2013 and 2016 sponsored by the Leverhulme Trust (Graham et al 2017, Turner et al 2021 enabled us to provide evidence that the topsoil incorporated components from earlier occupations, particu- larly from the disintegration of pottery used to contain brine in salt processing and the fuel used to heat the brine and drive off water to produce salt cakes. Topsoil nutrient capacity was higher than expected in what otherwise would be a mangrove wetland.…”
Section: Results So Farmentioning
confidence: 99%
“…Instead, the changes in fertility and the accumulation of deposits seem to reflect unintentional behaviour -the detritus of living, working and dying. Work carried out between 2013 and 2016 sponsored by the Leverhulme Trust (Graham et al 2017, Turner et al 2021 enabled us to provide evidence that the topsoil incorporated components from earlier occupations, particu- larly from the disintegration of pottery used to contain brine in salt processing and the fuel used to heat the brine and drive off water to produce salt cakes. Topsoil nutrient capacity was higher than expected in what otherwise would be a mangrove wetland.…”
Section: Results So Farmentioning
confidence: 99%
“…The study mapped complex patterns of Hg enrichment across the site in surface soils and temporally via sediment cores. Turner et al (2021) found the greatest concentrations of total Hg were in organic matter-rich anthrosols (a peak value of 1.3 μg g −1 detected near the centre of the site, adjacent to Maya structures) and in a low organic anthrosol containing ceramic, charcoal and obsidian fragments (0.78 μg g −1 ). Significantly, a comparable peak concentration (0.8 μg g −1 ) corresponding with 20th century fossil-fuel combustion atmospheric indicators in a 210 Pb-dated core from a site-adjacent pool.…”
Section: Marco Gonzalezmentioning
confidence: 93%
“…Mercury analysis of soils and sediments from Maya sites has been undertaken using a variety of analytical approaches meaning that direct comparisons between past datasets need to be undertaken with some caution (Turner et al, 2021). Most of the studies identified in our review detail the particle-size fraction of samples analysed for Hg content.…”
Section: Mercury Analytical Approachesmentioning
confidence: 99%
See 2 more Smart Citations